Pemanfaatan Limbah Jerami Menjadi Produk Briket Demi Meningkatkan Perekonomian Masyarakat di Desa Tanjung Qencono - Ricky Kurniawan; Yoga Edi Setiawan2; Ragil Saputra; Wisnu Febrianto; Tri Fauzia Rahma; Syntia Pertiwi6; Syifa Shandy Erlia; Tri Diana; Tia Ayu Lestari; Umi Salimah; et al. (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This study discusses efforts to utilize rice straw waste as a raw material for briquette production, aimed at improving the economy of the community in Tanjung Qencono Village, East Lampung. The majority of the village’s population works as farmers, whose income is still hampered by various factors such as low crop prices and pest attacks. Transforming rice straw waste into alternative briquettes is an innovative solution that optimizes local resources while producing economically valuable products. The methods used include site studies, research on production equipment, community training, and outreach on briquette utilization. Briquette production is adjusted to the harvest and planting seasons, with quality evaluated based on product density, moisture, and strength. The results show that the rice straw briquettes have good characteristics and competitive selling points. Community participation in the training strengthened understanding of environmentally friendly briquette production and use. Another positive impact is seen in reducing wood use, supporting environmental conservation and sustainability. This study concludes that the use of rice straw as a raw material for briquettes has the potential to be an economically and ecologically sound solution, strengthening community welfare and preserving the environment in the village. Further development efforts are strongly recommended to increase yields and achieve sustainable positive impacts.